Environmental health, economy, and amenities interactively drive migration patterns among China's older people - Wang, Hongjie; Gao, Xiaolu; Liu, Guili; Wang, Fuyuan; Rosenberg, Mark W. (Frontiers in Public Health, 2024)
The increasing older migrants is rapidly changing regional demographic and social structures. There is an urgent need to understand the spatial pattern and influencing factors of older migrants, especially the role of environmental health. However, this issue has been under-studied. This study put intra-provincial and inter-provincial older migrants as research subjects, estimated their spatial concentration index based on Iterative Proportional Fitting approach, and explored their influencing factors using GeoDetector Model. The results showed that: (1) In 2015, more than 76% of interprovincial older migrants were distributed in eastern China, and most intra-provincial older migrants were scattered in sub-provincial cities. (2) Compared to economy and amenities factors, single environmental health played a relatively weak role in older migration. The interaction between environmental health and economic-amenities become the key driving force of older migration. (3) There are significant differences in the dominant environmental health factors between interprovincial migration and intra-provincial migration, respectively temperature and altitude. Our findings can help policymakers pay attention to the composition of older migrants based on urban environmental health characteristics, and rationally optimize older care facilities layouts to promote supply-demand matching.